Medievalism in Nineteenth-Century Belgium: The 1848 Monument to Godfrey of Bouillon - Simon John (Medievalism, 2023)
On 15 August 1848, a bronze equestrian statue of the crusading hero Godfrey of Bouillon (d.1100) was unveiled in the Place Royale in Brussels, Belgium's capital. Conceived and largely funded by the national government, its creation was a major element in a programme of political and cultural consolidation put into place after the Belgian Revolution (1830-1831) and the consequent establishment of the nation's independence. From the outset, the monument was designed to transmit ideas about history and nationhood, and functioned as a focal point in discussions of politics, language, religion and identity.This book sheds new light on a range of dynamics in nineteenth-century Belgium, using the statue as a prism; it investigates responses to it both home and abroad, and traces broader national interest in the commemoration of Godfrey, adopted as a national hero despite being born almost 800 years before the emergence of the state. Above all, it reveals that Belgian politics and culture in this period were profoundly shaped by a sustained interest in the Middle Ages, and by efforts to shape a historical narrative that traced Belgian nationhood back to that era, and beyond.